Study Of The Combination Of Chicken Manure/urea And Watering Volume On The Growth Of Padi Sunggal (Oryza Sativa L.) Plant - Widata, Sri; Maryani, Yekti; Subagja, Hariadi; Fidianingrum, Dias Nur (International Journal of Technology, Food and Agriculture, 2025)
The study aims to examine the effects of chicken manure /urea and the volume of water in the growth of the many varieties of rice (oryza sativa). The task is carried out in the Village of Argorejo, sedayu district, l district, Yogyakarta. The design of the experiment used in this study is a Complete Random Design (RAL). Treatment of combination of chicken manure and urea by 80%; 20%; 50%; 50% and 20%; 80%. The volume of water is 300 ml, 600 ml, and 900 ml. Variable observations include plant height, number of wildlings, the weight of wet safes, the weight of dry safes. Analysis of the observations using 5% variant print continued with Duncan's multipe range test (DMRT) at increased 5%. Analysis shows that there is no interaction between the combination of fertilizers and the water-giving. There is a real difference in the treatment of volume of water in the growth variables.